(untitled) (Fiep Bulletin - online, 2016)
Popular culture characterizes the way of living of a population through regional foods, religion, dances, toys and games. However, factors such as urban growth, lack of security and public spaces for leisure, contributed to a decreasing number of children playing games of the popular culture. From the conception that these games can lead to a physical and cultural development, we see the school as a tool to rescue them in the children’s environment. So, this study aimed to identify the importance that teachers who teach the physical education classes attribute to games played on the popular culture, targeting the early years of elementary school in the city of Cascavel - PR. The sample consisted of nine teachers who taught the physical education classes in the early years of public and private schools. It is a descriptive research, instrumented by a questionnaire containing five questions. The collected data were analyzed using descriptive statistics with maximum and minimum percentages of the responses. From the data obtained, we could observe that most teachers graduated in Physical Education know what the games of popular culture are. However, when asked about the rescue of these games in their classes, the teachers revealed they use the popular toys sporadically as a strategy for the implementation of the analyzed games. In this context, these activities should be a part of the annual planning of the content covered for physical education teachers, because then the kids would have a full access to ludic moments that would prioritize the popular culture games. Besides, we think the specific academic formation on the area would help the achievement of the aimed success on the physical education classes.